2008
DOI: 10.1038/jhh.2008.119
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and biventricular hypertrophy in essential hypertension

Abstract: The metabolic syndrome (MS) is associated with structural and functional alterations of the left ventricle (LV); no evidence is available on the impact of the MS on the right ventricle (RV). To assess whether MS, as defined by the ATP III report, is associated with biventricular hypertrophy, a total of 286 hypertensive subjects (mean age 58.7±12.2 years) attending our outpatient clinic underwent the following procedures: (1) physical examination and standard clinic blood pressure (BP) measurement; (2) routine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
21
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 35 publications
(34 reference statements)
9
21
1
1
Order By: Relevance
“…Hypertensive and obese patients have a twofold risk of developing LVH 4 .Cuspidi [33] showed that obesity nearly doubled the risk of biventricular hypertrophy; while Ärnlöv [34] found it as the main risk factor among the components of the metabolic syndrome for cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive and obese patients have a twofold risk of developing LVH 4 .Cuspidi [33] showed that obesity nearly doubled the risk of biventricular hypertrophy; while Ärnlöv [34] found it as the main risk factor among the components of the metabolic syndrome for cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, routine echocardiography that is performed in hypertensive patients does not necessarily evaluate the right chambers. The findings of the study by Cuspidi et al 6 would suggest that the evaluation of the right side of the heart is worthwhile and should be recommended. This would clearly help improve the clinical assessment and management of human hypertension.…”
mentioning
confidence: 97%
“…5 Diabetes mellitus accelerates the development of LVH in patients with essential hypertension independent of arterial pressure. 4 In this issue of the Journal of Human Hypertension, Cuspidi et al 6 show that metabolic syndrome (MS) also accelerates the development of LVH, as hypertensive patients of both genders had more cardiac alterations when they have MS.Earlier studies have shown that hypertensive patients with MS are more susceptible to develop LVH than those without MS. 7-10 Mule et al 9 showed in 475 non-diabetic subjects with mild-to-moderate essential hypertension, of whom 40% had MS, that left ventricular mass was significantly higher in those with MS than in those without it. The relationship between MS and left ventricular mass was not affected by gender.…”
mentioning
confidence: 99%
See 2 more Smart Citations